THE IMPACT OF COMBINED THERAPY ON DOGS’ ORGANISMS UNDER A LOCAL FORM OF DEMODECOSIS - Dovhiy, Y. Y.; Kondrenko, L. V. (Scientific Progress & Innovations, 2020)
The research analysis on D. canis invasion intensity in sick dogs has shown that on the 10th day of their treatment the intensity index decreased from 15.4±0.62 to 5.6±0.21 tick specimens in a smear, and on the 20th day the living causative agents were not detected. The result was similar for animals which received “Dectomax” + sulphuric-tar liniment as well as to those that were treated on the scheme: “Dectomax”+ 25 % Waxworm extract + sulphuric-tar liniment with adding Waxworms. “Dectomax” showed its 100% effectiveness as to demodecosis causative agents, and the preparations of symptomatic therapy did not have any acaricidal activity as to D. canis. According to the results of every-day clinical examination of the first experimental group of dogs, the fissure and scratch marks healing on the infested dog skin areas were ob-served on the 12th day of treatment, changes of skin color on the one which is typical for non-infected areas happened on the 14th day, skin softening was registered on the 16th day and dogs’ hair growing was seen on the 19th day. Similar results were achieved on the 8th, 10th, 13th and the 15th days of treatment while using the preparations containing Waxworms (the second experimental group of dogs). Thus, on the 10th day of dogs’ treatment at applying “Dectomax”, sulphuric-tar liniment with adding Waxworms and 25 % Waxworm ex-tract, by 21.7 % less leucocytes were detected in dog blood than in the first experimental group. In the dogs of the second experimental group, the reduction of basophils (by 2.8 times, р<0.001), eosinophiles (by 37.4 %, р<0.001), young (by 45 %, р<0.001), and rod neutrophils (by 23.9 %, р<0.01) was achieved, as well as the increase in the number of polymorphils (by 16.7 %, р<0.05) as compared with the indices of dogs, that were treated with only “Dectomax” and sulphuric-tar liniment. The decrease in leucocytes num-ber in dog blood when adding 25 % Waxworm extract and sulphuric-tar liniment containing Waxworms means that active agents in these preparations speed up the recovery of animals’ systems and organs, reduce the intensity of inflammatory and allergic processes. The analysis of blood biochemical indices of dogs suf-fering from demodecosis in a local form has confirmed the stimulating effect of the preparations containing Waxworms on body recovery during decubation. On the 10th day of treatment, the animals treated with “Dectomax”, sulphuric-tar liniment adding Waxworms and with 25 % Waxworm extract had an increase in the number of hemoglobulin (by10.9 %, р<0.05), and the decrease in the amount of total bilirubin (by 25.3 %, р<0.001), as well as in ALT enzymes (by 33.8 %, р<0.01). The received data have shown that active substances of the preparations containing Waxworms speed up regeneration processes in dog organism dur-ing the recovery after being infected with a local form of demodecosis.